Acute thrombotic microangiopathic kidney injury due to Echis coloratus envenomation. (2nd April 2020) - Rahmani, Tzvi-Ran Ilan; Nasasra, Taysir; Fuchs, Lior; Almog, Yaniv; Lurie, Yael; Galante, Ori
Abstract: Introduction: We describe two cases of Echis coloratus envenomation associated with thrombotic microangiopathic acute kidney injury (AKI). Case presentation: Two patients, 39 and 70 years old, were hospitalized due to E. coloratus envenomation. Both were treated with anti-venom and blood products due to coagulopathy. Several hours after admission both developed acute kidney injury (creatinine 10.63 and 7.63 mg/dL) associated with hemolysis (lactate dehydrogenase 3858 and 2698 U/L) schistocytosis (49 and 6%) and thrombocytopenia (26 and 30 × 10 3 /µL). A disintegrin and metalloprotease with a thrombospondin type 1 motif, member 13 activity was measured only in patient number 2 and was within the normal limits. Both patients were treated with hemodialysis and plasmapheresis (4–6 courses). Both were discharged with normal platelet count, and no hemolysis. Their renal function improved gradually and hemodialysis was discontinued. Discussion: Following E. coloratus envenomation, both patients described developed hemolytic uremic syndrome-like thrombotic microangiopathy, with thrombocytopenia, intravascular hemolysis and severe AKI. Both recovered after combined treatment with hemodialysis and plasmapheresis. Conclusions: E. coloratus envenomation can cause HUS-like TMA.